Deletion of yeast YCA1 gene inhibits mitochondrial respiratory complex activity and induces apoptosis - Bui, Van Ngoc; Nguyen, Duc Duy (Academia Journal of Biology, 2025)
Mitochondria play a central role in energy metabolism and the respiratory chain. They also play a major role in programmed cell death or apoptosis. Reactive oxygen species (ROS) are generated through both exogenous and endogenous pathways and pose a significant damage to DNA, lipids, and protein. Mitochondrial DNA (mtDNA) damage could result in loss of expression of mitochondrial polypeptides, inhibition of mitochondrial activity, induction of apoptosis. Thus, the purpose of the present study is to investigate the role of the YCA1 gene by using the BY4741 (wild type) and specific knock-out yeast strains (∆yca1). The activity of this gene in the mitochondrial respiratory chain and cellular apoptosis in response to DNA damage triggered by methyl methanesulfonate (MMS) treatment would be elucidated by using flow cytometry, chromatography, and OxoPlate® assay.The findings indicated that fully functional yeast caspase-1 encoded by YCA1 significantly attenuates the intracellular ROS level, while deletion of YCA1 (∆yca1) results in gradual ROS accumulation upon MMS treatment, thereby introducing damage to mtDNA, leading to inhibition of mitochondrial activity and oxygen consumption. Subsequently, the absence of YCA1 leads to blockage in the mitochondrial electron transport chain (mtETC), repression of ATP synthesis, and fluctuation of cellular energy status (AEC). Altogether, high mitochondrial activity of the wild type acts as a protective mechanism against oxidative stress (ROS), whereas low mitochondrial activity of the ∆yca1 enhances susceptibility to ROS that strongly induce apoptosis. These findings suggest that fully functional YCA1 plays a major role in the protection of cell from DNA damage, while mutation of the YCA1 gene results in a reduction of the living mutant ∆yca1 cells accompanied with cell nucleic apoptosis.